Awareness and adoption of child restraint seats in cars in an Indian city - Shetty, Anil; Shetty, Shraddha (International Journal of Research in Medical Sciences, 2017)
Background: Protective measures for children like restraints and booster seats are seldom used in developing countries. The thriving Indian economy has resulted in booming car sales, particularly in urban areas, unfortunately the number of car crashes and accidents on roads have also increased manifold. Objective of current study was to evaluate the awareness and usage of child safety measures in cars in an Indian city. Methods: 150 parents were given a self-report questionnaire and their views, practices and attitude towards child restraint seats and booster seats were assessed. Results: Only 22% of parents used child restraints and 11% used booster seats. Among the users, 73% (infant seats) and 84% (booster seats) admitted to inadequate knowledge about installation and utilization. Conclusion: Usage and knowledge about child safety measures in cars is abysmal. Measures to improve adoption of car safety devices will have substantial and tangible benefits.